Disrupted trabecular bone micro‐architecture in middle‐aged male HIV‐infected treated patients. Issue 7 (17th May 2016) - Sellier, P; Ostertag, A; Collet, C; Trout, H; Champion, K; Fernandez, S; Lopes, A; Morgand, M; Clevenbergh, P; Evans, J; Souak, S; de Vernejoul, M‐C; et al.
Abstract : Objectives: HIV‐infected individuals are at increased risk of incident fractures. Evaluation of trabecular bone micro‐architecture is an important tool to assess bone strength, but its use has not yet been reported in middle‐aged HIV‐infected male individuals. The aim of the study was to compare bone micro‐architecture between HIV‐infected and HIV‐uninfected men. Methods: In this cross‐sectional study, 53 HIV‐infected male individuals with a mean (± standard deviation) age of 49 ± 9 years who had been receiving antiretroviral therapy including tenofovir disoproxil fumarate (DF) for at least 60 months were compared with 50 HIV‐uninfected male controls, matched for age and ethnic origin. We studied the volumetric bone density and micro‐architecture of the radius and tibia using high‐resolution peripheral quantitative computed tomography (HR‐p QCT). Results: Volumetric trabecular bone density was 17% lower in the tibia ( P < 10 −4 ) and 16% lower in the radius ( P < 10 −3 ) in HIV‐infected patients compared with controls. By contrast, the cortical bone density was normal at both sites. The tibial trabecular micro‐architecture differed markedly between patients and controls: bone volume/total volume (BV/TV) and trabecular number were each 13% lower ( P < 10 −4 for both). Trabecular separation and inhomogeneity of the network were 18% and 24% higher in HIV‐infected patients than in controls, respectively. The radial BV/TV and trabecular thickness were each 13% lower ( P < 10 −3 and 10 −2, respectively). Cortical thickness was not different between the two groups. Conclusions: The findings of lower volumetric trabecular bone density and disrupted trabecular micro‐architectural parameters in middle‐aged male HIV‐infected treated patients help to explain bone frailty in these patients.